The Decolonising Camera: Street Photography and the Bandung Myth - Lee, Christopher J. (Kronos: Southern African Histories, 2021)
This article examines the visual archive of the 1955 Asian-African Conference held in Bandung, Indonesia. Better known as the Bandung Conference or simply Bandung, this diplomatic meeting hosted 29 delegations from countries in Africa and Asia to address questions of sovereignty and development facing the emergent postcolonial world. A number of well-known leaders attended, including Jawaharlal Nehru of India, Zhou Enlai of China, Gamal Abdel Nasser of Egypt, and Sukarno of the host country, Indonesia. Given its importance, the meeting was documented extensively by photojournalists. The argument of this article is that the visual archive that resulted has contributed to the enduring symbolism and mythology of Bandung as a moment of Third World solidarity. More specifically, the street photography style of many images – with leaders walking down the streets of Bandung surrounded by adoring crowds – depicted an informality and intimacy that conveyed an accessible, anti-hierarchical view of the leaders who were present. These qualities of conviviality and optimism can also be seen in images of conference dinners, airport arrivals, delegate speeches, and working groups. Drawing upon the critical work of scholars of southern Africa and Southeast Asia, this article summarily positions the concept of the ‘decolonising camera’ to describe both the act of documenting political decolonisation as well as the ways in which visual archives produced during decolonisation can contribute to new iconographies of the political, which are both factual and mythic at once.